2023
DOI: 10.1039/d3sc01720f
|View full text |Cite
|
Sign up to set email alerts
|

A porphyrin-based molecular cage guided by designed local-electric field is highly selective and efficient

Shakir Ali Siddiqui,
Sason Shaik,
Surajit Kalita
et al.

Abstract: The present work outlines a general methodology for designing efficient catalytic machineries that can easily be tweaked to meet the demands of the target reactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Motivated by studies that have attributed encapsulation-mediated rate enhancements to the electrostatic environment provided by the cage, , we aimed to identify if encapsulation in the Ga 4 L 6 cage alters the electrostatic characteristics of TMCs. Specifically, we compared the ESP and partial charges at each TMC metal center in solvated and cage environments (see Section ).…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by studies that have attributed encapsulation-mediated rate enhancements to the electrostatic environment provided by the cage, , we aimed to identify if encapsulation in the Ga 4 L 6 cage alters the electrostatic characteristics of TMCs. Specifically, we compared the ESP and partial charges at each TMC metal center in solvated and cage environments (see Section ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, to enhance the catalysis, we engineered the cage so as to orient the local electric field along the reaction axis (i.e., the Fe–O axis). It was found that the engineered cage possesses a significant dipole moment along y -axis which interact with the LEF along the y -direction and slightly lowers the barrier for R -selective reaction . Inspired by this finding, strong R / S switchable cages were computationally engineered as well, as shown in Figure .…”
Section: Designed-lef (D-lef) To Achieve the Desired Activity Through...mentioning
confidence: 99%
“…In a very recent study, we have extended the scope of tailored local electric fields to supramolecular cages, and we have shown that such D-LEFs enable precise and tunable control over the catalytic environment, providing a highly flexible and adjustable platform for enhancing reactivity and selectivity. 73 Here, a computational approach was used to engineer a porphyrin-based cage (PB-1) 74 and to encapsulate the active oxidant (HM1) 75 and substrate (tetralin, TLN) 76 inside it. Subsequently, to enhance the catalysis, we engineered the cage so as to orient the local electric field along the reaction axis (i.e., the Fe–O axis).…”
Section: Designed-lef (D-lef) To Achieve the Desired Activity Through...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a light-absorbing molecule with the ability to activate oxygen, cobalt porphyrin has found wide applications in the field of photocatalysis. , For example, by inserting a single cobalt atom into the porphyrin skeleton, Li and coworkers significantly reduced the charge transfer resistance, inhibited electron/hole recombination, and broadened the light absorption, thereby significantly improving the photocatalytic performance . Introducing porphyrins into metal–organic cages as efficient photocatalysts is also considered as a highly effective strategy. , …”
Section: Introductionmentioning
confidence: 99%